1990
DOI: 10.1007/bf00404140
|View full text |Cite
|
Sign up to set email alerts
|

The relationships of concentrations of insulin, intact proinsulin and 32?33 split proinsulin with cardiovascular risk factors in Type 2 (non-insulin-dependent) diabetic subjects

Abstract: Standard radioimmunoassay for insulin may substantially overestimate levels of insulin because of cross-reaction with other insulin-like molecules. We have measured concentrations of insulin, intact proinsulin and 32-33 split proinsulin using two-site monoclonal antibody based immunoradiometric assays, and of insulin by a standard radioimmunoassay ("immunoreactive insulin") in 51 Type 2 (non-insulin-dependent) diabetic subjects in the fasting state. The relationships of these concentrations were sought with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
104
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(113 citation statements)
references
References 42 publications
(35 reference statements)
8
104
1
Order By: Relevance
“…19 This observation further supports that an increase in the concentrations of insulin precursors rather than the plasma insulin concentrations per se underlies the association with CHD. 6 It has been suggested that the association between immunoreactive plasma insulin and CVD may have been confounded by comorbidity in earlier cohort studies. 20 To circumvent such a possibility in the present study, subjects with CVD or malignant disease at baseline were excluded from our analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 This observation further supports that an increase in the concentrations of insulin precursors rather than the plasma insulin concentrations per se underlies the association with CHD. 6 It has been suggested that the association between immunoreactive plasma insulin and CVD may have been confounded by comorbidity in earlier cohort studies. 20 To circumvent such a possibility in the present study, subjects with CVD or malignant disease at baseline were excluded from our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that increased concentrations of insulin precursor molecules, rather than plasma insulin per se, constitute the association with CHD. 6 The extent to which PLMs contribute to the association between IRI and CHD is largely unknown. In a longitudinal study lasting up to 6.5 years, the significant relationship between proinsulin and CHD became nonsignificant when controlled for the confounding effect of body weight.…”
mentioning
confidence: 99%
“…Insulin was measured with a conventional immunoassay known to cross-react with proinsulin. Proinsulin levels are increased in diabetics and subjects with impaired glucose tolerance, 37 and some authors argue that this causes a false observation of an association between hyperinsulinemia and glucose tolerance. However, when proinsulin is taken into account, subjects with impaired glucose tolerance are still shown to have increased insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Another possibility is that proinsulin or proinsulin split products, rather than insulin per se, are involved, since NIDDM patients have an elevated basal ratio of plasma proinsulin to immunoreactive insulin and the concentration of PAI-1 in the plasma of these patients correlates more with the concentration of proinsulin and des 29,30 proinsulin than with insulin. 28 Finally, recent observations raise the possibility that insulin resistance rather than hyperinsulinemia may be involved. 29 Obviously, further studies are required to resolve these apparent inconsistencies in the human and animal insulin data.…”
Section: Insulin/proinsulinmentioning
confidence: 99%